2014
DOI: 10.1111/bju.12604
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for renal angiomyolipoma: outcomes and factors predictive of delayed intervention

Abstract: ObjectiveTo present the outcomes of active surveillance (AS) for renal angiomyolipomas (AMLs) and to assess the clinical features predicting delayed intervention of this treatment option. Patients and MethodsWe retrospectively reviewed the outcomes of patients diagnosed with AMLs on computed tomography (CT) who were managed with AS at our institution. The AS protocol consisted of 6-and 12-month, then annual follow-up visits, each one including a physical examination and CT imaging. Discontinuation of AS was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 25 publications
4
58
0
2
Order By: Relevance
“…No significant AS failures or deaths from any cause were reported. 56 These results are comparable with those reported in the smaller series by De Luca et al 53 Conversely, Mues et al did not find statistically significant correlations between clinical predictors (such as tumor dimension, growth rate or symptoms) and the need for active treatment. 52 In that study, among 91 patients diagnosed with AML, 48 were placed on AS as primary management.…”
Section: As For Benign Tumor (Angiomyolipoma)supporting
confidence: 78%
See 1 more Smart Citation
“…No significant AS failures or deaths from any cause were reported. 56 These results are comparable with those reported in the smaller series by De Luca et al 53 Conversely, Mues et al did not find statistically significant correlations between clinical predictors (such as tumor dimension, growth rate or symptoms) and the need for active treatment. 52 In that study, among 91 patients diagnosed with AML, 48 were placed on AS as primary management.…”
Section: As For Benign Tumor (Angiomyolipoma)supporting
confidence: 78%
“…With the aim to answer this relevant question, Ouzaid et al reported outcomes from a retrospective cohort of 130 patients diagnosed with AML on computed tomography imaging and managed with AS at the Glickman Urological and Kidney Institute. 56 The mean patient age was 53.3 ± 16.5 years, and the vast majority of enrolled patients were female (77.7%). A total of 70% of tumors were less than 4 cm at the time of diagnosis, and 28 patients (21%) were symptomatic (flank pain and hematuria).…”
Section: As For Benign Tumor (Angiomyolipoma)mentioning
confidence: 98%
“…Even though this is also a rational recommendation, it is unlikely to be fullfilled in many parts of subSaharan Africa. [1,2,10] In our group, 3 patients presented with cardiac rhabdomyomas, and 5 had lesions identified after TSC was diagnosed. It is possible that these additional cases reflected limited antenatal assessment, and further highlights the difficulties of early detection in our setting.…”
Section: Discussionmentioning
confidence: 72%
“…Ouzaid et al (69) found that only 13 out of 38 patients with AML >4 cm discontinued active surveillance after 4 years mean follow-up, arguing that treatment for all tumors >4 cm would have resulted in a 65% over-treatment rate and that 67% of symptomatic patients were managed with active surveillance without complications. Bhatt et al (64) found in their series of 447 patients up to 70% of asymptomatic lesions >4 cm with no difference in growth rates for lesions >4 and <4 cm.…”
Section: Discussionmentioning
confidence: 99%